Effect of Aqueous Stem Bark Extract of Khaya senegalensis on Some Biochemical, Haematological, and Histopathological Parameters of Rats - A. Onu; Y. Saidu; M. J. Ladan; L. S. Bilbis; A. A. Aliero; S. M. Sahabi (Journal of Toxicology)
The subchronic effect of aqueous stem bark extract of Khaya senegalensis on some biochemical, haematological, and histopathological parameters of rats was investigated. The rats were divided into six groups of five rats per group. Groups I to VI were administered graded doses of 0, 400, 800, 1200, 1600, and 2000 mg/kg bw, respectively. The result of study revealed that administration of the Khaya senegalensis for twenty-eight days at the experimental dose resulted in significant (P<0.05) increase in urea, electrolytes (Na+, K+), and creatinine levels. The extract also significantly (P<0.05) increased serum activity of ALT, AST, and ALP. The levels of protein, albumin, and bilirubin were significantly changed when compared to their control values, but they were not dose dependent. The hematological indices assayed in this study were not significantly affected at the experimental dose when compared to the control values. Histological studies of the liver showed cellular degeneration and necrosis and bile duct hyperplasia and fibrosis with lymphocytic infiltration of the hepatocyte, providing supportive evidence for discussing the biochemical findings, indicative of functional derangement. The histological architecture of the kidney and that of the heart were however preserved. The result of this study indicates that the aqueous stem bark extract of K. senegalensis may affect the cellular integrity of vital organs of the body.